PROSPECTIVE TEACHERS’ EVALUATIONS OF TEACHING PRACTICE IN AN INCLUSIVE CLASSROOM - Margevica-Grinberga, Ieva; Laganovska, Egija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Today’s teachers must be ready to address all students, whatever their abilities, needs, and knowledge. Prospective teachers must develop the necessary competencies during their studies to ensure inclusive education for all pupils. Teaching practice remains one critical means of exposing future teachers to actual classroom experiences to equip them with pedagogical skills. The course followed in this study included teaching practice to allow future teachers to put their theoretical knowledge into practice. The research aimed to analyse future teachers’ feedback after teaching practice in an inclusive classroom. These data – the prospective teachers’ findings after the teaching practice – were analysed using content analysis. The sample of the study consisted of 97 future teachers. The results showed that the student teachers faced various challenges, e.g. needing more experience in an inclusive setting, creating activities that included all students, and needing more teaching resources. However, most were optimistic about the opportunity to put the knowledge they gained during the course into practice. Therefore, teacher educators should ensure that students are prepared for entry into the teaching profession and have a positive pedagogical experience in an inclusive classroom. The teacher educators should also have sufficient knowledge and skills to work with all pupils.